ASTROMETRY AND PHOTOMETRY WITH PLATE SCANS FROM STERNBERG ASTRONOMICAL INSTITUTE'S PHOTOGRAPH COLLECTION (FIRST EXPERIENCES - Mironov, A. V.; Nikolaev, F. N.; Tuchin, A. S.; Zakharov, A. I.; Levkova, K. F. (Одеські астрономічні публікації, 2017)
A scanning of plates from Sternberg astronomical institute's photograph collection has began to create a library of digital images. A large number of new variable stars has already discovered using the scans. It is shown that it is possible to carry out an astrometry with an error about a half of a pixel and a photometry with an error about 0,15 mag.